Preliminary research on grindability improvement of coal by microwave pretreatment - Zhu, Xiangnan; Tao, Youjun; Sun, Qixiao; Song, Ao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2017)
Physicochemical Problems of Mineral Processing. Vol. 53, 2017, Issue 1, s. 644–655
Keywords: mineralogia - czasopisma; przeróbka kopalin; mineralurgia; inżynieria mineralna; metalurgia ekstrakcyjna; separacja; wzbogacanie; coal; microwave pretreatment; grindability; moisture reduction; liberation

An innovative technology for recovery of zinc, lead and silver from zinc leaching residue - Zheng, Yong-xing; Lv, Jin-fang; Liu, Wei; Qin, Wen-qing; Wen, Shu-ming (Oficyna Wydawnicza Politechniki Wrocławskiej, 2016)
Physicochemical Problems of Mineral Processing. Vol. 52, 2016, Issue 2, s. 943–954
Keywords: mineralogia - czasopisma; przeróbka kopalin; mineralurgia; inżynieria mineralna; metalurgia ekstrakcyjna; separacja; wzbogacanie; zinc leaching residue; lead sulfate; zinc sulfate; reduction roasting; flotation

Improvement of chalcopyrite atmospheric leaching using controlled slurry potential and additive treatments - Jafari, Mustafa; Karimi, Gholamreza; Ahmadi, Rahman (Fizykochemiczne Problemy Przeróbki Kopalin, 2017)
Physicochemical Problems of Mineral Processing. Vol. 53, 2017, Issue 2, s. 1228–1240
Keywords: mineralogia - czasopisma; przeróbka kopalin; mineralurgia; inżynieria mineralna; metalurgia ekstrakcyjna; separacja; wzbogacanie; chalcopyrite; improved leaching; controlled oxidation-reduction potential; additive treatment; pyrite; sodium chloride; silica

Response of energy-size reduction to the control of circulating load in vertical spindle pulverizer - Li, Hong; He, Yaqun; Zhang, Yu; Ge, Zhenzhou; Xie, Weining; Wang, Shuai; Li, Ke (Fizykochemiczne Problemy Przeróbki Kopalin, 2017)
Physicochemical Problems of Mineral Processing. Vol. 53, 2017, Issue 2, s. 793–801
Keywords: mineralogia - czasopisma; przeróbka kopalin; mineralurgia; inżynieria mineralna; metalurgia ekstrakcyjna; separacja; wzbogacanie; circulating load control; response of energy-size reduction; mixture grinding; energy efficiency

Exposition time analysis of AlGaN/GaN HEMT fabrication by electron beam lithography - Indykiewicz, Kornelia; Paszkiewicz, Bogdan; Paszkiewicz, Regina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Optica Applicata, Vol. 49, 2019, nr 1, s. 161-166
Keywords: optyka; electron beam lithography (EBL); device fabrication; exposition time reduction

Propozycja redukcji kosztów w realizacji dostaw w centrum miasta na przykładzie Jeleniej Góry - Lewandowski, Krzysztof (The proposition of mutual reduction of delivery cost in the city center on the example of Jelenia Góra, 2015)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2015, Nr 383, s. 95-107
Keywords: logistyka miejska; koszt; redukcja; ugoda; city logistics; cost; reduction; agreement

Speckle reduction by angle diversity using a translucent spatial light modulator - Tong, Zhaomin; Chen, Xuyuan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2012)
Optica Applicata, Vol. 42, 2012, Nr 3, s. 651-658
Keywords: optyka; spatial light modulator (SLM); grating; speckle reduction

Study on recovery of lead, zinc, iron from jarosite residues and simultaneous sulfur fixation by direct reduction - Yayun Wang; Huifen Yang; Weihao Zhang; Ronglong Song; Bo Jiang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Physicochemical Problems of Mineral Processing. Vol. 54, 2018, Issue 2, s. 517-526
Keywords: jarosite; direct reduction; recovery; valuable metal; sulfur fixation

Energy Security Versus the Pursuit of CO₂ Emission Reductions - Wierzbiński, Marcin (Bezpieczeństwo energetyczne a dążenie do redukcji emisji CO₂, 2010)
The author tries to answer the question if energy security is consistent with the pursuit of CO2 reduction. The problem is depicted from four perspectives, that is from international, national, regional and energy consumers’ perspective.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 173-180
Keywords: energy security; CO2 emission reduction; climate change

Noise reduction for digital holograms in a discrete cosine transform (DCT) domain - Choi, Hyun-Jun; Seo, Young-Ho; Kim, Dong-Wook (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
This paper presents a method for reducing noise in a digital hologram, which occurs during acquisition. The algorithm proposed initially transforms a digital hologram into frequency-domain data through a discrete cosine transform (DCT), and separates the object from the background in the transformed image. As a noise reduction method, a histogram modification method is applied to the object, while the background is substituted with zero values. Experimental results showed that the proposed scheme improves the visual image quality very much when reconstructed by both the optical system and the PC simulation.
Optica Applicata, Vol. 40, 2010, nr 4, s. 991-1005
Keywords: optyka; digital hologram; noise reduction; discrete cosine transform (DCT); holographic reconstruction

Accuracy improvement of bulk optical polarization interferometric sensors - Wierzba, Paweł; Kosmowski, Bogdan B. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Interferometric sensors using bulk optical components exhibit very high measurement resolution. In order to attain high accuracy, these sensors are often implemented as polarization interferometers, in which stable and well-defined states of polarization are maintained. Unwanted phenomena degrading accuracy of this class of sensors are discussed in the paper. Signal processing technique which improves accuracy of polarization interferometric sensors is presented. Its implementation using analogue circuits is discussed and a method of improving its performance is devised.
Optica Applicata, Vol. 35, 2005, nr 1, s. 171-185
Keywords: optyka; optical sensing; interferometry; polarization; displacement measurement; homodyne interferometers; nonlinearity reduction; polarization mixing; beamsplitters

Feature selection methods in datamining techniques - Ziemba, Paweł; Piwowarski, Mateusz (Metody selekcji cech w technikach data mining, 2011)
Data mining techniques are largely based on machine learning algorithms. They are to serve to extract data models which, due to their large information content, are not recognized by people. Data redundancy poses a problem both for data mining algorithms as well as people, which is why various methods are used in order to reduce the amount of analyzed data, including data mining methods such as feature selection. The article outlines basic issues linked with feature selection and contains an analysis of five feature selection algorithms belonging to the filter category. Results obtained by each method were validated with the help of CART decision tree algorithms. The CART analysis revealed that the results of each of the five algorithms are acceptable
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 213-223
Keywords: data mining; dimension reduction; feature selection; feature filters; redukcja ilości danych; selekcja cech; filtry cech

Zróżnicowanie rozwoju społeczno-gospodarczego w powiatach województwa wielkopolskiego - Spychała, Marcin (Differentiation of the socio-economic development in the districts of the Wielkopolska Voivodeship, 2017)
W opracowaniu określono poziom rozwoju społeczno-gospodarczego powiatów województwa wielkopolskiego na podstawie 53 wskaźników ujętych w ramach 5 czynników rozwoju regionalnego: kapitału ludzkiego, kapitału społecznego, kapitału materialnego, kapitału finansowego oraz innowacyjności. Celem artykułu jest przedstawienie zróżnicowania przestrzennego poziomu rozwoju społeczno-gospodarczego województwa wielkopolskiego w układzie powiatów. Poziom rozwoju społeczno-gospodarczego oraz poziom rozwoju jego czynników zostanie określony na podstawie miernika syntetycznego ukazującego odległość taksonomiczną danego powiatu od przyjętego wzorca rozwoju. W artykule postanowiono zweryfikować hipotezę, według której rozwój społeczno-gospodarczy w powiatach województwa wielkopolskiego jest mocno zróżnicowany, a najwyższy jego poziom odnotowuje się w dużych miastach regionu – Poznaniu, Lesznie, Kaliszu i Koninie
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 487, s. 293-305
Keywords: miernik syntetyczny; redukcja Hellwiga; odległość od wzorca; synthetic indicator; Hellwig’s reduction; distance from the model

Redukcja odpadu wynikającego z błędów wizualnych z wykorzystaniem metody DMAIC - Herter, Magdalena; Lesiów, Tomasz (Reduction of the waste resulting from visual errors using the DMAIC method, 2015)
Celem pracy było określenie skuteczności wykorzystania metody DMAIC do redukcji odpadu wynikającego z błędów wizualnych podczas produkcji filtrów do wody w przedsiębiorstwie X. W pracy użyto metody case study oraz wykorzystano metody jakościowe do pomiaru i analizy danych. Zaprezentowano i przedyskutowano wyniki projektu przeprowadzonego przy wykorzystaniu narzędzi DMAIC (Define – definiuj, Measure – mierz, Analyze – analizuj, Improve – ulepszaj, Control – nadzoruj). Zastosowanie tej metody skutkowało usystematyzowaniem działań przeprowadzanych podczas projektu, zidentyfikowaniem czynników powodujących defekty wizualne filtrów, określeniem najważniejszych przyczyn występowania odpadów, poprawą procesu produkcji i kontroli, zwiększeniem świadomości kadry pracowniczej i dostosowaniem procesu produkcji, tak aby finalny produkt w jak największym stopniu spełniał oczekiwania konsumenta
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2015, Nr 4 (19), s. 9-31
Keywords: Six Sigma; DMAIC; jakość; redukcja odpadu; usprawnianie procesu; quality; waste reduction; process improvements

An Analysis of Excavation Support Safety Based on Experimental Studies - Gorska, Karolina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2015)
Studia Geotechnica et Mechanica, Vol. 37, 2015, nr 3, s. 19-29
Keywords: geotechnika - czasopisma; mechanika - czasopisma; soldier-pile wall; inclinometer measurements; φ/c reduction procedure

Mutual correlation of sol-gel optical properties and repeatability of production process examined by statistical pattern recognition methods - Kobel, Joanna; Podbielska, Halina; Lechna-Marczyńska, Monika; Ulatowska-Jarża, Agnieszka (Oficyna Wydawnicza Politechniki Wrocławskiej, 2003)
Optica Applicata, Vol. 33, 2003, nr 1, s. 97-105
Keywords: optyka; sol-gel matrix; physical properties; repeatability of production; pattern recognition; dimensionality reduction; cluster analysis

The variation in the level of the socio-economic development of the NUTS-3 subregions in the European Union - Spychała, Marcin (Publishing House of Wroclaw University of Economics and Business, 2023)
A very important research problem is the specification of the level of the socio-economic development of the EU regions. Within the cohesion policy, one may differentiate between regions more and less advanced in terms of general development, including the worth of GDP per capita. Following that measure, one can establish the areas eligible for getting help from EU budget support programmes. The purpose of the article was to present the variation in the level of the socio-economic development of 28 EU countries within the 1,347 NUTS-3 units. The level of the development was established on a multilevel basis, subcategorising three factors of regional development: human capital, the natural environment and the economy. The article specifies the extent of the NUTS-3 unit general progression following the analysis of 31 indicative measures structured around publicly available Eurostat statistical data (as of 2019). The extent of the progression was demonstrated based on a synthetic measure revealing the taxonomic distance of a particular region from the assumed arrangement measuring the development. The research procedure consisted of five development levels, namely: the establishment of factors of the progression of regions, a choice of variable factors, a decrease in the multi-factor space, an identification in the extent of the social and economic progression of the researched units and a subcategorisation of the units on the scale of the social and economic progression structured around a ranking prepared using the analysis of a lowering synthetic measure. The research resulted in spatial variation of 1,347 NUTS-3 unit subregions in 28 EU states presented in terms of the level of the social and economic progression and the three subparts of the progression. The highest synthetic measure was noted in the areas including the capitals of the states included in the research and in a belt comprising the Irish subregions, Central England, the Benelux states, Western and Southern Germany, up until the Alpine subregion. Moreover, significant differences between the levels of the development within the respective states were presented. The results of the research may be a source of inspiration for EU institutions within the scope of the manner of specifying the richest and the poorest EU regions, whose purpose is to ensure the efficient introduction and conclusion of the cohesion policy in the programming periods specified.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 179-203
Keywords: regional development; NUTS-3 units; developmental discrepancies; distance from the pattern; Hellwig’s data reduction

The main aspects of energy management - Wierzbiński, Marcin (Research Papers of Wrocław University of Economics, 2012)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2012, Nr 263, s. 182-190
Keywords: energy management; energy effectiveness; CO2 emission reduction; economic effectiveness; zarządzanie energią; efektywność energetyczna; redukcja emisji CO2; efektywność ekonomiczna

Wybrane aspekty gospodarki finansowej szpitali - Kister, Agnieszka (Selected problems of the financial economy of hospitals, 2016)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2016, Nr 440, s. 256-267
Keywords: gospodarka finansowa; przyczyny redukcji kosztów; źródła finansowania; szpitale; financial economy; causes of costs reduction; sources of business financing; hospitals

Poziom rozwoju społeczno-gospodarczego powiatów w Polsce - Spychała, Marcin (The level of socio-economic development of the districts in Poland, 2018)
W artykule dokonano analizy poziomu rozwoju społeczno-gospodarczego powiatów w Polsce na podstawie 43 wskaźników ujętych w ramach 4 czynników rozwoju regionalnego: kapitału ludzkiego materialnego, kapitału finansowego, kapitału ludzkiego oraz innowacyjności. Celem artykułu jest określenie zróżnicowania poziomu rozwoju społeczno- gospodarczego Polski w układzie powiatów. Poziom rozwoju społeczno-gospodarczego, a także poziom rozwoju jego czynników zostanie przedstawiony na podstawie syntetycznego miernika ukazującego odległość taksonomiczną danego powiatu od ustalonego wzorca rozwoju. W opracowaniu postanowiono zweryfikować hipotezę, według której rozwój społeczno- gospodarczy powiatów w Polsce jest mocno zróżnicowany, a najwyższy jego poziom odnotowuje się w największych miastach będących jednocześnie stolicami województw: Warszawie, Krakowie, Wrocławiu, Poznaniu, Gdańsku i Katowicach
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 527; s. 242-254
Keywords: miernik syntetyczny; powiaty; odległość od wzorca; redukcja Hellwiga; synthetic indicator; district; distance from the model; Hellwig’s reduction

Zmiana sprzedawcy energii elektrycznej jako sposób redukcji kosztów przedsiębiorstwa - Kotłowska, Mariola (Changing electricity suppliers as a way to reduce the costs of a company, 2013)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2013, Nr 289, s. 304-313
Keywords: rynek energii elektrycznej; redukcja kosztów; zmiana sprzedawcy; negocjowanie cen; electricity market; reduction of costs; change of a seller; negotiation of prices

Aspekty planowania sieci produkcyjnych małych i średnich przedsiębiorstw funkcjonujących w klastrach - Saniuk, Sebastian; Cheba, Katarzyna; Szopik-Depczyńska, Katarzyna (Network production planning aspects of small and medium enterprises operating in clusters, 2015)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2015, Nr 382, s. 376-388
Keywords: klastry; planowanie zleceń produkcyjnych; redukcja kosztów produkcji; wariantowanie sieci produkcyjnych; clusters; production orders planning; production costs reduction; prototyping of production networks

Inclusiveness of economic growth in emerging Asian and European economies - Sobański, Konrad (Research Papers of Wrocław University of Economics, 2012)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2012, Nr 257, s. 59-69
Keywords: economic growth; inclusive growth; income inequality; poverty reduction; South East Asian economies; Central and Easter European economies; wzrost gospodarczy; nierówności dochodów; ubóstwo

What Were the Reasons for the Rapid Landslide Occurrence in “Piaseczno” Open Pit? – Analysis of the Landslide Process - Jakóbczyk, Joanna; Cała, Marek; Stopkowicz, Agnieszka (Oficyna Wydawnicza Politechniki Wrocławskiej, 2015)
Studia Geotechnica et Mechanica, Vol. 37, 2015, nr 1, s. 25-35
Keywords: geotechnika - czasopisma; mechanika - czasopisma; landslide; open pit mine; slope stability analysis; numerical modelling; Limit Equilibrium Method (LEM); Shear StrengthReduction Method (SSRM)